Diagnostic and Prognostic Role of HER2 Genes in Breast Carcinoma - Nabeel Baqer Al Besher et al. (International Journal of Scientific Research and Innovative Studies, 2024)
HER2 (human epidermal growth factor receptor 2) is a pivotal biomarker and therapeutic target in breast carcinoma, overexpressed or amplified in approximately 15-20% of cases. Its presence is associated with aggressive disease behavior and poor prognosis. Accurate assessment of HER2 status through immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) is essential for diagnosis and treatment planning. HER2-targeted therapies, such as trastuzumab, have revolutionized the management of HER2-positive breast cancer, significantly improving patient outcomes. However, challenges such as resistance to therapy and tumor heterogeneity persist, necessitating ongoing research. This review discusses the diagnostic and prognostic roles of HER2 in breast carcinoma, highlighting the impact of targeted therapies and the need for further advancements in treatment strategies. Keywords: HER2, Breast Carcinoma, Diagnostic, Prognostic. Received Date: July 07, 2024 Accepted Date: July 28, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/178 DOI: https://doi.org/10.5281/zenodo.13399174